Unbalanced biclique cryptanalysis of a full round Midori. Issue 5 (1st March 2019) - Han, Guoyong; Zhang, Wenying; Xing, Zhaohui; Zhao, Hongluan; Lian, Jian
Abstract : Midori is a family of lightweight block ciphers presented by Banik et al . at Asiacrypt 2015. Biclique cryptanalysis is a typical key‐recovery attack that is proposed to attack the full AES by Bogdanov et al . in ASIACRYPT 2011. The method can attack a great deal of ciphers utilising the main idea of MITM attack and the basic principle of the biclique structure. In this study, the authors first provide an unbalanced biclique attack on full round Midori with partial matching and precomputation. They demonstrate that full round Midori64/128 are not secure against unbalanced biclique attacks. They construct a five‐round 4 × 8 unbalanced biclique on Midori64, with data complexity of 2 36 and time complexity of 2 126.25 by investigating the simple key schedule and the encryption structure. Furthermore, they present a four‐round 8 × 16 unbalanced biclique on Midori128 with data complexity of 2 72 and computational complexity of 2 126.91 . To the best of authors' knowledge, the result is the best single‐key cryptanalytic result of Midori.